Anti-influenza effects of Aloe vera gel on MDCK cells: protective efficacy against ultraviolet-C exposure and analysis of biochemical characteristics and microbial activities - Rasha A. Al-Eisa; Rokayya Sami; Ruqaiah I. Bedaiwi; Roqayah H. Kadi; Suzan A. Abushal; Doaa Mahmoud Johari; Afnan M. Alnajeebi; Reham M. Algheshairy; Abeer A. Abu-Zaid; Sami A. Al-Dhumri (Frontiers in Sustainable Food Systems)
The main objective of the current study was to examine the anti-influenza effects of Aloe vera gel on the Madin–Darby Canine Kidney (MDCK) cell line, as well as its protective efficacy against ultraviolet-C exposure, by studying its biochemical characterization and microbial activities. The lowest IC50 value (4.23 mg/mL) was reported for the treated cells, with a concentration of 8 mg/ML of Aloe vera extract after contamination with the AP/R/8 virus. After 2 h of ultraviolet-C exposure, all cells in the control group and those with single-sided gel application died, while the cells treated with the gel on both sides showed 29.000 viable cells. The lowest inhibition activity was detected against Bacillus subtilis (2.20 mm) at a concentration of 20 μL. In comparison, the highest inhibition activity was observed against Pseudomonas aeruginosa (21.29 mm) at a concentration of 100 μL. The highest values were detected in the Aloe vera gel samples in the following sequence: magnesium (28.43 mg/100 g), phosphorus (2.98 mg/100 g), zinc (143.01 μg/100 g), selenium (137.18 μg/100 g), iron (19.78 μg/100 g), chromium (15.40 μg/100 g), aluminum (12.35 μg/100 g), and vanadium (8.70 μg/100 g). On the other hand, trace elements such as cadmium, cobalt, and nickel showed the lowest concentrations (0.05, 0.12, and 0.23 μg/100 g, respectively). The plant contained high quantities of phenols, flavonoids, tannins, saponins, and anthraquinones, along with high antioxidant activity (1,1-diphenyl-2picrylhydrazyl, DPPH) and ascorbic acid content. Based on these observations, it can be concluded that Aloe vera plants contain variable compounds that may be responsible for their therapeutic and pharmacological uses.